Blood pressure variability after iIntravenous thrombolysis in acute stroke does not predict intracerebral hemorrhage but poor outcome - Kellert, Lars; Sykora, Marek; Gumbinger, Christoph; Herrmann, Oliver; Ringleb, Peter A. (Cerebrovascular diseases, 2012)
Background: The relevance of blood pressure variability (BPV) in the development of intracerebral hemorrhage (ICH) after intravenous thrombolysis (IVT) in acute stroke still remains uncertain. Methods: 427 consecutive patients treated with IVT in the years 2007-2009 were studied. Blood pressure (BP) values were analyzed from admission to follow-up imaging scan and described as mean, maximum, minimum, standard deviation (SD), difference between maximum and minimum, successive variation (SV) and maximum SV. ICH was categorized based on radiologic criteria and symptomatic ICH (sICH) was defined as ICH plus worsening of the National Institute of Health Stroke Scale by ≧4 points or leading to death. Three-month outcome was described by means of the modified Rankin Scale. Results: We observed any ICH in 51 (11.9%) and sICH in 10 (2.3%) patients. Systolic and diastolic BP profiles, including mean, maximum, minimum, SD, difference between maximum and minimum, SV and maximum SV, did not differ between ICH-negative, ICH-positive and sICH patients. In univariate analysis, high systolic BPV was associated with sICH (p = 0.03). A logistic regression model to predict ICH only found early CT findings (OR = 2.74, 95% CI = 1.47-5.11, p < 0.01) as independently associated with ICH. Poor 3-month outcome was independently predicted by age (OR = 0.96, 95% CI = 0.94-0.97, p < 0.001), NIHSS on admission (OR = 0.84, 95% CI = 0.80-0.87, p < 0.001), ICH (OR = 0.29, 95% CI = 0.13-0.66, p < 0.01) and high systolic BPV (OR = 1.68, 95% CI = 1.05-2.69, p < 0.05). Conclusions: We demonstrate that high BPV in patients receiving IVT leads to poor outcome but does not increase the risk of ICH/sICH.